Population Movements Towards Dhaka: Disquiets And Commendations - Al Amin, Mohammad Mastak; Rana, Md. Shohel; Kalam, Iftekhar Mohammad Shafiqul (European Scientific Journal, ESJ, 2017)
Internal migration is now a significant constituent for policy issues in Bangladesh, so there is a need to strengthen the statistical resources devoted to monitoring population movements which directly track migrants and provide household level data. The main objective of our study was to examine the factors and characteristics of individual’s internal migration towards Dhaka city, Bangladesh and recommend some policy issues. We considered a sample of 448 individuals from the rural and urban areas of Bangladesh those migrated to Dhaka city. Here we tried to figuring the determinants of socio-economic, economic and environmental factors related with the internal migration. We tried to interpret the differences between individual’s income, occupational positions, years of schooling, educational facilities and wealth of family before and after migration process. We found that the significant factors liable for internal migration were mainly occupational, educational and climatic. Ordinary least square technique was applied on three regression models which indicated that there were differences due to internal migration regarding to these economic, demographic and environmental factors in Bangladesh. Also we tried to recommend some policies and instruments about the future policy of internal migration.